2011
DOI: 10.1016/j.neuropharm.2010.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of hypocretin/orexin neurons in the lateral hypothalamus by nociceptin/orphanin FQ blocks stress-induced analgesia in rats

Abstract: We recently demonstrated that hypocretin/orexin (Hcrt) and nociceptin/orphanin FQ (N/OFQ) systems coordinately regulate nociception in a mouse model of stress-induced analgesia (SIA). However, the site of N/OFQ action on modulation of SIA was elusive, since N/OFQ was administered via intracerebroventricular (i.c.v.) injection acting on widely distributed N/OFQ receptors (NOP) in the brain. In the present study, we tested the hypothesis that N/OFQ modulates the SIA directly via the inhibition of the Hcrt neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Hypocretins participate in regulating ethanol reward and re-establishment of ethanol seeking through actions in the LH and VTA (Dayas et al, 2008; Lawrence et al, 2006). It is plausible that withdrawal associated CRF activation in the LH elevates hypocretin release (Winsky-Sommerer et al, 2004) altering the activity of N/OFQ neurons that have recently been discovered to make synaptic contacts with hypocretin neurons in the LH (Gerashchenko et al, 2011). Indeed, in the LH, N/OFQ blocks stress-induced analgesia via direct inhibition of hypocretin neurons (Gerashchenko et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypocretins participate in regulating ethanol reward and re-establishment of ethanol seeking through actions in the LH and VTA (Dayas et al, 2008; Lawrence et al, 2006). It is plausible that withdrawal associated CRF activation in the LH elevates hypocretin release (Winsky-Sommerer et al, 2004) altering the activity of N/OFQ neurons that have recently been discovered to make synaptic contacts with hypocretin neurons in the LH (Gerashchenko et al, 2011). Indeed, in the LH, N/OFQ blocks stress-induced analgesia via direct inhibition of hypocretin neurons (Gerashchenko et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that withdrawal associated CRF activation in the LH elevates hypocretin release (Winsky-Sommerer et al, 2004) altering the activity of N/OFQ neurons that have recently been discovered to make synaptic contacts with hypocretin neurons in the LH (Gerashchenko et al, 2011). Indeed, in the LH, N/OFQ blocks stress-induced analgesia via direct inhibition of hypocretin neurons (Gerashchenko et al, 2011). It is therefore reasonable to speculate that an analogous mechanism contribute to anxiety triggered by the ethanol abstinence and that the increased NOP gene expression in the LH may represent an up-regulation to counteract CRF-induced hyperactivity of hypocretin neurons during withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Both electrical (Lopez and Cox,1992; Dafny et al,1996; Franco and Prado, 1996) and chemical stimulation with S -glutamate (Behbehani et al, 1988), morphine (Dafny et al, 1996; Franco and Prado, 1996), carbamylcholine (carbachol; Holden & Naleway, 2001; Holden et al, 2002; Holden et al, 2005; Holden and Pizzi, 2008; Holden et al, 2009; Safari et al, 2009), or nociception/orphanin FQ (Gerashchenko et al, 2011;) increase response latencies to acute (nociceptive) pain in rats. This nociceptive modulation was found in both male (Dafny et al, 1996; Franco and Prado, 1996; Behbehani et al, 1988; Safari et al, 2009; Gerashchenko et al, 2011) and female rats (Lopez and Cox, 1992; Holden and Naleway, 2001; Holden et al, 2002; Holden et al, 2005; Holden and Pizzi, 2008; Holden et al, 2009). The role of the LH in modulating neuropathic pain states is not known for either male or female rats.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 They project broadly throughout the brain and mediate many physiological functions, including wakefulness and sleep, energy homeostasis, glucose metabolism, autonomic function, 2-11 and stress-adaptive responses such as stress-induced analgesia. 12, 13 Loss of Hcrt neurons or dysfunction in the Hcrt system has been observed in several disorders, including narcolepsy 14, 15 and subarachnoid hemorrhage. 16 Recently, a few studies have indicated that the Hcrt system may be involved in cerebral ischemic injury.…”
Section: Introductionmentioning
confidence: 99%